Data Protection Strategy in Management Information Systems: Risk Analysis and Implementation - Widagdo, Nanda Ari Wahyu; Winasis, Afiat Lintang; Putri, Fanisa Halya; Wardana, Fhatoni Nur; Pamekas, Bondan Wahyu (IC-ITECHS, 2024)
Management information system (MIS) data protection is critical and cannot be ignored, especially considering the increasing number of cyber threats and data leaks that can harm organizations. This journal discusses various data protection methods that can be used in MIS, with special emphasis on risk analysis and good implementation. In this research, we conducted a comprehensive analysis of the various threats faced by management information systems, including threats from cyberattacks, human error, and technological vulnerabilities. We also identify the components that contribute to those risks and how they impact data integrity and confidentiality. We do this using a case study approach and qualitative data collection. Additionally, the journal offers various solutions for mitigation, such as implementing strict access controls, data encryption, and security training for users. We also emphasize how important it is to have a clear information security policy and disaster recovery procedures to ensure continued operations. This research aims to assist organizations in strengthening their management information systems by providing practical, evidence-based recommendations for implementing data protection strategies. It is hoped that the results will serve as a guide for stakeholders in designing and implementing effective data protection strategies, which will increase trust and security in data management in the digital era.